The disproportionate risk burden of CT scanning on females and younger adults in Australia: a retrospective cohort study - David A. Gibson; Rachael E. Moorin; James Semmens; D'Arcy J. Holman (Elsevier, 2014)
Abstract Objectives: To explore the interaction of computed tomography (CT) use, dose and radiation risk of Australian Medicare‐funded CT scanning and the impact on cancer incidence and mortality. Methods: This retrospective cohort study used records of Medicare subsidised CT scans in Australia (2006/07 to 2011/12) and Australian CT dosimetry. The annual number, rate and adjusted likelihood of CT were determined for gender, age and examination type. Incident cancer and cancer‐related mortality attributable to CT in Australia were estimated using lifetime attributable risk coefficients, dosimetry and scan numbers. Results: The number of CT scans increased by 36% from 2006/07 to 2011/12. Only patients aged 0-4 years did not present an increase in CT scanning rates. Females were 11% more likely to be scanned than males. Head, abdomen/pelvis and spine CT scans were the most likely areas scanned. Females were attributed 61% of both incident cancers and cancer‐related mortality from 55% of scans performed. Patients aged 15-44 years were attributed 37% of incident cancers and 30% of cancer‐related mortality from 26% of CT scans. Conclusions: CT in Australia is increasing, including in groups at higher risk from ionising radiation. This presents a complex set of risk/benefit considerations for clinicians and policy makers.